EFEKTIVITAS REBUSAN KAYU MANIS DAN KEMANGI TERHADAP TEKANAN DARAH - Awaluddin Awaluddin; Atika Dewi (LPPM Universitas Abdurrab, 2025)
Hypertension is a common health problem in the elderly and can cause various serious complications if not treated properly. This study aims to determine the effectiveness of cinnamon and basil leaf decoction on lowering blood pressure in elderly hypertension in Sialang Baru Village, Siak Regency, Riau Province. The research method used is quantitative with pre-post experimental sampling technique. This study involved 40 respondents who were divided into two intervention groups of cinnamon bark decoction and basil leaf decoction. Blood pressure measurements were taken before and after the intervention for seven days. The statistical test used was the Wilcoxon test. The results showed that there was a significant decrease in blood pressure after the administration of cinnamon bark decoction, with a median value before intervention of 166.23 mmHg and after intervention to 155.58 mmHg (p < 0.05). Similarly, in the basil leaf decoction group, the median blood pressure value before the intervention was 167.44 mmHg and after the intervention became 156.16 mmHg (p < 0.05). The analysis showed that cinnamon bark decoction was more effective than basil leaf decoction in reducing blood pressure in the elderly.